2022
DOI: 10.3390/ma16010012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al and La Doping on the Structure and Magnetostrictive Properties of Fe73Ga27 Alloy

Abstract: The changes of microstructure, magnetostriction properties and hardness of the Fe73Ga27−xAlx alloy and (Fe73Ga27−xAlx)99.9La0.1 alloy (x = 0, 0.5, 1.5, 2.5, 3.5, 4.5) were studied by doping Al into the Fe73Ga27 and (Fe73Ga27)99.9La0.1 alloy, respectively. The results show that both the Fe73Ga27−xAlx alloy and (Fe73Ga27−xAlx)99.9La0.1 alloy are dominated by the A2 phase, and the alloy grains are obvious columnar crystals with certain orientations along the water-cooled direction. A proportion of Al atoms replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Du et al studied the changes of microstructure, magnetostriction properties and hardness of the Fe73Ga27−xAlx alloy and (Fe73Ga27−xAlx)99.9La0.1 alloy (x = 0, 0.5, 1.5, 2.5, 3.5, 4.5) by doping Al into the Fe73Ga27 and (Fe73Ga27)99.9La0.1 alloy, respectively [ 8 ]. The results indicated that trace La doping can improve the magnetostriction properties and deformation resistance of Fe-Ga alloy, which provides a new design idea for the Fe-Ga alloy, broadening their application in the field of practical production.…”
Section: Soft Magnetic Alloys and Compositesmentioning
confidence: 99%
“…Du et al studied the changes of microstructure, magnetostriction properties and hardness of the Fe73Ga27−xAlx alloy and (Fe73Ga27−xAlx)99.9La0.1 alloy (x = 0, 0.5, 1.5, 2.5, 3.5, 4.5) by doping Al into the Fe73Ga27 and (Fe73Ga27)99.9La0.1 alloy, respectively [ 8 ]. The results indicated that trace La doping can improve the magnetostriction properties and deformation resistance of Fe-Ga alloy, which provides a new design idea for the Fe-Ga alloy, broadening their application in the field of practical production.…”
Section: Soft Magnetic Alloys and Compositesmentioning
confidence: 99%